ANÁLISIS DE LA SITUACIÓN FINANCIERA PARA EL CENTRO DE ACCIÓN SOCIAL “MATILDE HIDALGO” EN LA CIUDAD DE LOJA, PERIODO 2013 - 2015 - Cabrera, Claudia Geovanna (2018)
With the development of the present thesis called Analysis of the Financial Situation for the Center of Social Action "Matilde Hidalgo" in the City of Loja, period 2013-2015 entity that is part of the Provincial Council of Loja. For the execution of the same, it was drawn as a general objective; "Carry out an analysis of the financial situation for the Social Action Center" Matilde Hidalgo "in the city of Loja, 2013-2015 period", in order to know the situation of the same; which was achieved by 'setting specific objectives: how to collect the necessary information to perform the financial analysis, perform a vertical and horizontal analysis of CASMH financial statements, apply financial indicators derived from the balance sheets and how to recommend alternatives based on the results obtained. In order to comply with the first objective, it was necessary to carry out an investigation of the theoretical part, both accounting and budgetary, in order to carry out an interview with the accountant and the financial manager and request the general statements for the realization of the practical part in which the data in the form of tables and graphics with their corresponding interpretations; the second objective is about vertical analysis to the years 2013 - 2015 of the balance sheet and income statements, which allowed knowing the economic and financial behavior of the institution, achieving a detailed analysis of the accounts and establishing how it is in its liquidity, solvency and profitability; the horizontal analysis shows the following increases and decreases in the financial statements, and when analyzing there are some difficulties that are not favorable for the development of the CASMH; as a third objective, financial indicators were applied to the public sector in order to know the level of efficiency, profitability, liquidity, debt capacity of the same; Subsequently to meet the fourth objective after the study of the balance sheets highlight the main problems of the Matilde Hidalgo Center and thus be able to give alternative 5 recommendations based on the results obtained that can be accepted by the organization that will improve the situation of the institution. The following methods were used in the same way: Deductive that served to extract more relevant bibliographic information for financial analysis, and in the same way to develop the theoretical framework, until reaching the conclusion conclusion and recommendations of the research work. In this way, the inductive is applied which was used for the internal diagnosis of the financial department of the Center, with the purpose of knowing the weaknesses or the existence of a problem of the social assistance center. And finally, the analytical that was used to interpret the results obtained from the information of the financial statements through vertical analysis, horizontal analysis and determine financial indicators in order to establish alternative solutions to the problem encountered. Finally, with these considerations the conclusions and recommendations are pointed out, where in the analyzed period some inconsistencies are observed, with the Government Accounting Regulations that affect the financial analysis process of the Financial Statements. And in this way focus on giving guidance such as the restructuring of the Financial Statements as the Result based on the Government Accounting policies that guide the accounting process and in this way generate consistent, relevant, verifiable and understandable information that are issued by the Ministry of Finance of Ecuador in accordance with the provisions of the Organic Code of Planning and Public Finance and in this way provide information on the economic and financial evolution of the entity that is useful for the purpose of rendering accounts, and making decisions.